Identificación de regiones expuestas a bajas temperaturas en el Perú usando imágenes de la temperatura de la superficie del suelo procedente de sensor MODIS/Aqua - Aguilar-Lome y Col., Jaime (2019)
Land Surface Temperature (LST) is a key variable in the interactions and energy fluxes between the Earth surface and the atmosphere. The MODIS LST nighttime at spatial resolution of 1 km was analyzed during the period 2003-2017 (June-August) over Peru to identify regions exposed to low temperatures. Our result shows that the regions below 0°C are above 3500 masl (in average). In addition, the mean monthly nighttime LST is correlated with the mean monthly minimum air temperature (R = 0.96, N = 763) and the topography significantly influences the variability of LST.